2006
DOI: 10.1126/science.1127592
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Induced Acute Recruitment of Circulating Endothelial Progenitor Cells to Tumors

Abstract: The contribution of bone marrow-derived circulating endothelial progenitor cells (CEPs) to tumor angiogenesis has been controversial, primarily because of their low numbers in blood vessels of untreated tumors. We show that treatment of tumor-bearing mice with vascular disrupting agents (VDAs) leads to an acute mobilization of CEPs, which home to the viable tumor rim that characteristically remains after such therapy. Disruption of this CEP spike by antiangiogenic drugs or by genetic manipulation resulted in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
456
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 526 publications
(487 citation statements)
references
References 17 publications
24
456
1
5
Order By: Relevance
“…19,20 Treatment of tumor-bearing mice with vascular disrupting agents recruited EPCs to the tumors. 21 In patients with hepatocellular carcinoma, CD 133 + EPCs incorporated into tumor vessels. 22 In contrast to these studies, no contribution of bone marrow-derived cells to tumorigenesis was found by others.…”
Section: Epcs In Tumor Angiogenesismentioning
confidence: 99%
“…19,20 Treatment of tumor-bearing mice with vascular disrupting agents recruited EPCs to the tumors. 21 In patients with hepatocellular carcinoma, CD 133 + EPCs incorporated into tumor vessels. 22 In contrast to these studies, no contribution of bone marrow-derived cells to tumorigenesis was found by others.…”
Section: Epcs In Tumor Angiogenesismentioning
confidence: 99%
“…Although the molecular pathways involved in EPC mobilization remain to be determined, several stimuli including VEGF, stroma cell derived factor-1a (SDF-1a), placental growth factor (PlGF), granulocyte colony stimulating factor (G-CSF) and estrogens were described to be involved in the mobilization of EPC from the bone marrow to tumor sites [31,[34][35][36][37][38][39]. VEGF can activate matrix metalloproteinase-9 which that cleaves the membrane-bound stem cell cytokine mKit Ligand in bone marrow stromal cells, to liberate soluble sKit Ligand, which then stimulates cKitpositive EPC to migrate from a quiescent bone marrow niche to a permissive microenvironment, activating EPC from a quiescent to a proliferative state [40].…”
Section: Molecular Mechanism Of Epc Mobilizationmentioning
confidence: 99%
“…Thus, the significantly higher levels of EPC paralleling clinical severity suggest the possible relevance of these cells in metastatic progression of tumors, and point out their potential use as biomarker and/or target in cancer therapy. Surprisingly, Shaked et al [38] found that treatment of tumor-bearing mice with vascular disrupting agents, which target the established but abnormal tumor vasculature, leads to an acute mobilization of EPC. These cells subsequently colonize the viable tumor rim that usually remains after such therapy, and drives ''rebound revascularization'' and tumor regrowth/recovery.…”
Section: Clinical Applications: Epc As Biomarker and Therapeutic Target?mentioning
confidence: 99%
“…Subsequent studies in which authors scrutinized the contribution of CEPs to tumor blood vessels have had conflicting results, and a consensus on the extent and functional significance of this phenomenon is still lacking (6)(7)(8). In more recent studies, investigators also have suggested that certain cytotoxic drugs, such as vascular-disrupting agents (VDA) and taxanes, increase the number of CEPs in the peripheral blood of mice and enhance their incorporation in the tumor vasculature (9,10). VDAs are microtubule-destabilizing drugs that cause the rapid collapse of intratumoral blood vessels, leading to tumor necrosis and shrinkage.…”
Section: In the Spotlight Introductionmentioning
confidence: 99%
“…Shaked and colleagues (9) have previously shown that a single VDA dose induces a transient CEP spike in the mouse circulation as soon as 4 hours after drug administration. Neutralization of this CEP spike with the use of a blocking antibody against vascular endothelial growth factor receptor-2 (VEGFR-2) inhibited the incorporation of CEPs in the tumor blood vessels and delayed tumor revascularization and regrowth (9).…”
Section: In the Spotlight Introductionmentioning
confidence: 99%